Research Test on Formative Assessment Product - Syafriani, Agustina (International Journal of English Language and Pedagogy, 2023)
The development of a formative assessment instrument is supposed to be based on the components of Asesmen Kompetensi Minimum (AKM / Minimum Competency Assessment). The components consist of content, cognitive processes and context and the instrument including the content of informational texts and socio-cultural and scientific contexts. However, in the cognitive process component, the textbook used in Grade X SMA Negeri 1 Pangkalan Susu North Sumatera provides information only. It does not include interpretation and integration, evaluation, and reflection. Furthermore, in line with the rules of the AKM, it is necessary to analyse the competency components measured according to the learning level for class X. 1. This research using a Feasibility study investigated the formative assessment of historical recount text based on AKM in reading skills for class X. This product based on the item validation process can be used as a formative assessment. The product formative assessment of historical recount text based on AKM in reading skills becomes a reference for teachers to prepare formative assessments or other assessments based on AKM. This is to familiarize and prepare students for the National Assessment specific to AKM. This conclusion comes from a result of testing data from material experts, Indonesian language teacher assessments and student responses.